2016
DOI: 10.1093/ntr/ntw007
|View full text |Cite
|
Sign up to set email alerts
|

Social Disparities in Unaided Quit Attempts Among Daily Current and Former Smokers: Results From the 2010–2011 Tobacco Use Supplement to the Current Population Survey

Abstract: This study used the most recent nationally representative data for the United States to examine sociodemographic disparities in unaided quitting among current and former daily smokers who made a quit attempt in the last 12 months. Most quit attempts were unaided. People who were male, younger, non-Hispanic black, had lower nicotine dependence, and those who were low income were more likely to make an unaided quit attempt. These results could be used by policy makers and program planners to develop cessation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
4
20
0
Order By: Relevance
“…There were relevant differences between those who made pharmacologically unassisted quit attempts and those who used medications, and between those who used varenicline and those who used TNP. Our findings reflect those recently reported by McCarthy and colleagues (2016) in their analysis of the TUS-CPS data, focusing on socioeconomic disparities among those making unassisted quit attempts. Those making unassisted quit attempts were more likely to self-identify as racial/ethnic minority and had lower income than those reporting use of smoking cessation medications.…”
Section: Discussionsupporting
confidence: 91%
“…There were relevant differences between those who made pharmacologically unassisted quit attempts and those who used medications, and between those who used varenicline and those who used TNP. Our findings reflect those recently reported by McCarthy and colleagues (2016) in their analysis of the TUS-CPS data, focusing on socioeconomic disparities among those making unassisted quit attempts. Those making unassisted quit attempts were more likely to self-identify as racial/ethnic minority and had lower income than those reporting use of smoking cessation medications.…”
Section: Discussionsupporting
confidence: 91%
“…This finding suggests that the administration of free NRT may be received better in the UC setting, but further research to explore the reasons for interest in NRT is warranted. Similar to other research 24 , 28 , 29 , we also found that parents who were Black or more motivated to quit were more receptive to cessation efforts. These findings are clinically relevant to decision-making about NRT.…”
Section: Discussionsupporting
confidence: 89%
“…In some studies, spontaneous quitters are suggested to have more years of education and higher incomes, to be more likely to have a partner, to have fewer smokers in their social network, and to have a smoking history indicative of a lower level of nicotine addiction [46-48]. These characteristics suggest that self-quitters face fewer barriers for cessation and may have more resources to support their efforts to achieve and maintain abstinence.…”
Section: Discussionmentioning
confidence: 99%